Interactions Between the Serotonergic and Other Neurotransmitter Systems in the Basal Ganglia: Role in Parkinson’s Disease and Adverse Effects of L-DOPA - Muñoz, Ana; Lopez-Lopez, Andrea; Labandeira, Carmen M.; Labandeira-Garcia, Jose L. (Frontiers in Neuroanatomy, 2020)
Parkinson’s disease (PD) is characterized by the progressive loss of dopaminergic neurons in the substantia nigra. However, other non-dopaminergic neuronal systems such as the serotonergic system are also involved. Serotonergic dysfunction is associated with non-motor symptoms and complications, including anxiety, depression, dementia, and sleep disturbances. This pathology reduces patient quality of life. Interaction between the serotonergic and other neurotransmitters systems such as dopamine, noradrenaline, glutamate, and GABA controls the activity of striatal neurons and are particularly interesting for understanding the pathophysiology of PD. Moreover, serotonergic dysfunction also causes motor symptoms. Interestingly, serotonergic neurons play an important role in the effects of L-DOPA in advanced PD stages. Serotonergic terminals can convert L-DOPA to dopamine, which mediates dopamine release as a “false” transmitter. The lack of any autoregulatory feedback control in serotonergic neurons to regulate L-DOPA-derived dopamine release contributes to the appearance of L-DOPA-induced dyskinesia (LID). This mechanism may also be involved in the development of graft-induced dyskinesias (GID), possibly due to the inclusion of serotonin neurons in the grafted tissue. Consistent with this, the administration of serotonergic agonists suppressed LID. In this review article, we summarize the interactions between the serotonergic and other systems. We also discuss the role of the serotonergic system in LID and if therapeutic approaches specifically targeting this system may constitute an effective strategy in PD.